2023
DOI: 10.4102/phcfm.v15i1.3688
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, attitude and practice on screening and early diagnosis of prostate cancer of primary health care providers in the Free State

Abstract: Background: Prostate cancer is topmost in terms of incidence and mortality among men in sub-Saharan Africa, including South Africa. Prostate cancer screening is beneficial only to certain categories of men, making a rational screening approach necessary.Aim: This study aimed to assess the knowledge, attitudes and practice (KAP) regarding prostate cancer screening among primary health care (PHC) providers in the Free State, South Africa.Setting: Selected district hospitals, local clinics and general practice ro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…Using Bloom's cut-offs, knowledge was classified into poor knowledge (<60 %), moderate knowledge (60-79%) and high knowledge (80-100 %). 16 The majority of the participants had moderate knowledge of safe sex practices (41.2%) (Figure 1). An independent student t-test was used to measure mean knowledge differences according to gender, place of birth, religion, major in studies, place of residence and sexuality.…”
Section: Resultsmentioning
confidence: 99%
“…Using Bloom's cut-offs, knowledge was classified into poor knowledge (<60 %), moderate knowledge (60-79%) and high knowledge (80-100 %). 16 The majority of the participants had moderate knowledge of safe sex practices (41.2%) (Figure 1). An independent student t-test was used to measure mean knowledge differences according to gender, place of birth, religion, major in studies, place of residence and sexuality.…”
Section: Resultsmentioning
confidence: 99%
“…KAP assessment questionnaires have been developed and used in highly prevalent malignancies such as cervical, prostate and gastrointestinal cancers [22][23][24]. A Chinese cross-sectional study among healthcare workers found moderate knowledge and positive attitudes regarding early gastrointestinal cancers [24].…”
Section: Discussionmentioning
confidence: 99%
“…Among health system-related factors, researchers have documented attitudes of health workers [ 12 , 22 ], inadequate facilities [ 16 ], perceived affordability [ 18 , 23 , 24 ], and access to care and information [ 16 , 23 , 25 ]. Based on these studies, empirical data on how individual characteristics and health system factors are associated with PCa screening varies both in findings and recommendations.…”
Section: Introductionmentioning
confidence: 99%